Prehospital management of exertional heat stroke at sports competitions: International Olympic Committee Adverse Weather Impact Expert Working Group for the Olympic Games Tokyo 2020 - Hosokawa, Y.; Racinais, S.; Akama, T.; Zideman, D.; Budgett, R.; Casa, D. J.; Bermon, S.; Grundstein, A. J.; Pitsiladis, Y. P.; Schobersberger, W.; Yamasawa, F. (British Journal of Sports Medicine, 2021)
Objectives: This document aimed to summarise the key components of exertional heat stroke (EHS) prehospital management.